The Effect of Concentrated Institutional Portfolio on Stock Returns - ZHANG, Hao li (Institutional Knowledge at Singapore Management University, 2009)
This paper examines whether stock return is related to the extent of portfolio concentration on the part of institutional fund managers. There is evidence that large firms are preferred for both concentrated and well-diversified funds. Also, a trading strategy based on concentrated ownership generates positive abnormal return. This implies that informational effect (implied in an increase in concentrated capital) has significant impacts and predictability on returns. Meanwhile, we do not find diversified ownership has predictability on future stock returns.